Effective piezoelectric energy harvesting with bandwidth enhancement by assymetry augmented self-tuning of conjoined cantilevers. (January 2019) - Staaf, L.G.H.; Smith, A.D.; Lundgren, P.; Folkow, P.D.; Enoksson, P.
Highlights: Efficient vibration piezoelectric energy harvester. Asymmetric conjoined cantilevers yield broader bandwidth. Mechanical self-tuning has positive impact on bandwidth. Abstract: Vibrational energy harvesting offers a potential power supply for future intelligent wireless sensors. In order to make vibrational energy harvesters more useful, a broad bandwidth is desirable since many vibrations are stochastic in nature. In this paper we use a piezoelectric self-tuning energy harvester to demonstrate the importance of designing for asymmetry in a system of conjoined cantilevers. Asymmetry is achieved by varying the piezoelectric cantilever lengths as well as the proof mass weights. In addition to bandwidth broadening, a self-tuning effect is experimentally demonstrated by a sliding mass. The measurement results confirm previous model predictions. Graphical abstract: